Formal and informal practices in contemporary Korean management. Issue 22 (16th December 2019) - Yang, Inju; Horak, Sven
Abstract: South Korean human resource management (HRM), characterized by lifetime employment and seniority-based promotion, has been suggested as an important factor contributing to the growth of Korean companies. However, the Asian financial crisis in 1997, raised questions about these practices, and Korean HRM underwent drastic changes, mainly by adopting a more flexible labor market approach. Despite Korean companies' efforts since then to change their HRM to a more western (US) style, much research indicates persistent challenges, both domestically and internationally. In an attempt to explain the challenges, we argue, in this conceptual paper, that it is necessary to consider the informal organization of Korean management in relation to formal organization. We suggest there are complementary overlaps and close integration between formal and informal organizational modes in Korean management. We fill a gap in the literature on the role of informal organization with indigenous Asian notions supporting the balance of opposition.